Workload, Job Stress, and Employee Performance in Digital Hospital Administration: A Cross-Sectional Study of Hospital Administrative Staff - Lysa Kurniati; Qurratul Aini (Malahayati Nursing Journal, 2026)
ABSTRACT The digitalization of hospital administration through the implementation of Hospital Management Information Systems (SIMRS) and electronic medical records has transformed the characteristics of administrative work. This transformation has increased cognitive demands, time pressure, and task complexity, which may affect workload, job stress, and employee performance. This study aimed to analyze the effects of workload and job stress on the performance of hospital administrative staff in the digitalization era. This research employed an explanatory quantitative approach with a cross-sectional design. The study was conducted among administrative staff at RSUD Bangil, Pasuruan Regency, in February 2026. A total of 98 respondents were selected using purposive sampling based on criteria that required participants to be administrative employees who actively used digital systems in their daily tasks. Workload was measured using the adapted NASA Task Load Index (NASA-TLX), while job stress and employee performance were assessed using standardized questionnaires. Data were analyzed using multiple linear regression at a 5% significance level. The findings indicated that workload had a positive and statistically significant effect on employee performance (p 0.05). Job stress also showed a positive and significant effect on performance (p 0.05). Simultaneously, workload and job stress significantly influenced employee performance, with a coefficient of determination of 50.8%, indicating that both variables explained more than half of the variance in performance. Workload and job stress are important determinants of administrative employee performance in a SIMRS-based hospital environment. Effective workload management and job stress control are essential strategies to support the sustainability and effectiveness of digital transformation in healthcare services.  Keywords: Workload, Job Stress, Employee Performance, Hospital Information System, Digital Administration.